JOB REPLACEMENT ARTIFICAL INTELLIGENCE DI INDUSTRI JASA: TINJAUAN PUSTAKA SISTEMATIS - Ika Diyah Candra Arifah; Mahaning Indrawaty Wijaya; Silviana Mar'atus Sholihah (Jurnal Ilmu Manajemen, 2022)
By performing a variety of activities, artificial intelligence (AI) is increasingly altering the service industry, providing a key source of innovation while jeopardizing human jobs. This double-edged effect is considered by the theory of AI job replacement. The idea provides four business intelligences necessary for service jobs — mechanical, analytical, intuitive, and empathic — and outlines how businesses should choose between humans and technology to complete these tasks. This study aims to describe how artificial intelligence (AI) is replacing human labour in the service industry and the sorts of business intelligence that AI will replace. Data from Scopus journal articles published between 2011 and 2021 will be analysed in a thorough literature review. VOS Viewer 1.6.17 was used to map and cluster (SLNA) the literatures collected over the last 10 years using Publish and Perish software. The network analysis of these articles showed keyword co-occurrence networks. According to the findings of the study, AI job replacement happens at the job level. First, AI augments a service job's work, a transitional stage known as augmentation, before eventually taking over all of a job's functions and eliminating the need for human labour. This study enrich the body of knowledge about the human resource management in industrial revolution and practical knowledge about talent management which suggest the service workers about the advancement of AI task substitution from low to high intelligence which has a predictable effect on their roles. Artificial Intelligence (AI) is gradually displacing human analytical skills, but the necessity of intuitive and empathic skills for service professionals is increasing, therefore new approaches of human–machine interaction are still required for delivering service excellence.